Accelerated Vesting in Takeovers: The Impact on Shareholder Wealth. Issue 1 (31st October 2012) - Elkinawy, Susan; Offenberg, David
<x xml:space="preserve">Abstract</x> We study the impact of accelerated vesting of equity awards on takeovers, whereby the restricted stock and/or stock options of the target chief executive officer (CEO) immediately vest and become unrestricted upon the close of the acquisition. We find that takeover premiums are significantly larger when the target CEO receives the benefit of accelerated vesting as compared to target firms with CEO's that continue to vest in their awards after closing the deal. Our evidence suggests that these cash windfalls triggered by accelerated vesting are beneficial to shareholders in completed deals. Accelerated vesting appears to be an efficient form of ex ante managerial contracting.